Information and communication technology in the field of school sport – Reality and challenges - كوندة سلمى (sports creativity, 2025)
This study aimed to identify the current use of information and communication technology (ICT) in school sports, by examining the various modern technologies that help teachers deliver their lessons effectively to students. The researcher employed a qualitative approach, relying on interviews conducted with physical education teachers in middle and high schools in the municipality of Salah Bey. The results concluded that ICT contributes significantly and effectively to the development of school sports.